Finite element models updating by means of a global approach - Aiad, Abdelkrim; Tawfiq, Imad (Computer Assisted Methods in Engineering and Science, 2007)
Analytical models are often used to analyse behaviour of structures, particularly in the field of structural dynamics. The application of such models demands that they must predict the effects of structural modifications with a reasonable accuracy. Unfortunately, lacks of correlation between initial analytical predictions and experimental results are usually observed so that the analytical model needs to be updated with respect to an experimental reference. Many updating methods, involving two main categories of techniques, have been developed in recent years. In the first group of methods, the model to be adjusted is modified by means of correcting parameters associated with the regions containing dominant errors in modelling. The techniques require a localization of modelling errors and are essentially iterative. The second category involves one-step algorithms to globally correct the model in terms of its representative mass and stiffness matrices. These methods have come to be called direct or global methods. Each class of methods presents advantages and disadvantages. The main disadvantage of the iterative methods is the errors localization phase that may require an extensive amount of computational efforts. In addition, the convergence is not ensured for all iterative algorithms. The present paper deals with a direct approach to correct the whole mass and stiffness matrices of a derived finite element model. A modal analysis and a quantitative study of matrix changes are performed to evaluate the capability of the proposed algorithm and to investigate its potential usefulness in model updating.